2023
DOI: 10.1097/aci.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of vernal keratoconjunctivitis in sub-Saharan Africa

Abstract: Purpose of review Vernal keratoconjunctivitis (VKC) is a chronic bilateral allergic inflammatory disease of the conjunctiva and cornea that affects children and young adults, especially in sub-Saharan Africa. A limbal form (tropical endemic limbo conjunctivitis) is thought to be more common in the tropics where research on this vision-impairing condition is scanty. We sought to review current literature from sub-Saharan Africa, with a focus on the prevalence of VKC and its clinical presentation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(86 reference statements)
0
3
0
Order By: Relevance
“… 33 , 34 , 35 This case‐control study is the first which focused exclusively on assessing the prevalence and risk factors associated with VKC in a large clinical cohort in Ghana. The prevalence of VKC among the study sample is within the middle bracket reported for most SSA countries that is, 2.30%−37% 32 but within the upper limit of reported cases in Europe (ranges from 1.2 to 10.6 cases per 10,000 population). 36 The high prevalence in SSA has been linked to the hot climatic conditions in such countries as Ghana, poor socioeconomic status, air pollution, and other comorbidities.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“… 33 , 34 , 35 This case‐control study is the first which focused exclusively on assessing the prevalence and risk factors associated with VKC in a large clinical cohort in Ghana. The prevalence of VKC among the study sample is within the middle bracket reported for most SSA countries that is, 2.30%−37% 32 but within the upper limit of reported cases in Europe (ranges from 1.2 to 10.6 cases per 10,000 population). 36 The high prevalence in SSA has been linked to the hot climatic conditions in such countries as Ghana, poor socioeconomic status, air pollution, and other comorbidities.…”
Section: Discussionmentioning
confidence: 54%
“… 37 The variation in the prevalence has been attributed to the diverse geographic and climatic spread. 32 This gives credence to the necessity for jurisdictional‐specific prevalence studies of VKC and further supported the region‐to‐region variation within the same country. The prevalence of 9.45%, though at the point of care could be far less than what exists in the population because barely half of the children (the most affected age group) receive care, and for those who do only 17% visit the clinic two times in a year.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation